Some thoughts about remembering the past as the foundation of peace building - Aćimović Dragan (Temida)
The author answered the Victimology Society’s call for the proposals about constructive ways of dealing with the past in Serbia. In this paper he is presenting his main ideas in that regard: celebration of the Day for the truth and reconciliation, cooperation between different groups within the society and development of positive memory.